Korelasi Keterampilan Membaca Pemahaman Teks Deskripsi dengan Keterampilan Menulis Teks Deskripsi Siswa Kelas VII SMP Negeri 1 Bonjol - Zahara, Dina; Afnita, Afnita (UNIB Press, 2020)
The purpose of this study was to determine the relationship between the reading comprehension skills of the descriptive text and the writing skills of the seventh grade students of SMP Negeri 1 Bonjol. This research used quantitative research using a descriptive correlational design. In this study, there were two variables, namely the X variable and the Y variable. The X variable was the reading comprehension skill, while the Y variable was the description text writing skill. The research instruments were objective tests and performance tests. The data of this study are the results of the reading comprehension skills test and the results of the descriptive text writing skills test. The test results were compared using the t-test formula to determine the correlation between the reading comprehension skills and the descriptive text writing skills of the seventh grade students of SMP Negeri 1 Bonjol. There are three results in this study. First, the reading skills of grade VII students of SMP Negeri 1 Bonjol are in good qualifications with an average score of 81.65. Second, the writing skills of the seventh grade students of SMP Negeri 1 Bonjol are in good qualifications with an average score of 78.58. Third, based on the results of the t-test, it can be concluded that there is a relationship between comprehension reading skills and the descriptive text writing skills of seventh grade students of SMP Negeri 1 Bonjol.